From Communities of Practice to Smart and Connected Communities: Information Sharing Practices Among Social Service Providers. Issue 1 (14th October 2022) - Slota, Stephen C.; Nigam, Ishan; Fleischmann, Kenneth R.; Greenberg, Sherri R.; Cruz, David
ABSTRACT: To be a smart and connected community is an aspiration and orientation. A goal of smart and connected communities is to make more effective and consistent use of data, information, and technology, and in many ways to operate at a critical junction between community members and an imagined future structured around a particular vision of the role of government, the role of participation, and often‐conflicting visions of what these might become. This paper reports findings from 32 semi‐structured interviews with stakeholders in the City of Austin Continuum of Care (CoC), a collaborative group of organizations working to end homelessness in the Austin/Travis County region, as well as critical analysis of their collaborative and siloed data resources. The key themes that emerged in this case study include the continual process of "becoming" a smart and connected community, focusing on the development and "accretion" of data and informational infrastructure, and its impact on the communities of practice related to providing services to people experiencing homelessness. The information behaviors of the stakeholders of the CoC demonstrates ongoing movement towards more collaborative resolutions of issues of data quality and interoperability, alongside a negotiation of the role of data‐intensive structuring of collaborations and work.